Quando a religião sobe ao palco: uma análise das contestações católicas à encenação de “Jesus Cristo Superstar” - Renan William dos Santos; Camila Assunção Crumo (Ciências Sociais Unisinos)
This article aims to map the controversy that arose with the exhibition of the play “Jesus Christ Superstar” in São Paulo in 2014. After a brief review of the ambiguous relations between the religious and artistic spheres (in the Weberian sense), it seeks to clarify the main discursive categories and strategies of action mobilized by the religious agents who sought to bar the exhibition of this play. Finally, it is shown how the notion of “blasphemy” is used to put the ideal of laicity itself at the center of the debate.